Design of the Monitoring System for Communication Satellite Information Security Based on Spaceborne Network Probe - Mingjian WANG; Dandan FAN; Xiaoshen XU; Meng LI (天地一体化信息网络)
To enhanced the information security protection capability of communication satellites and solved the information security monitoring problem of the system under the condition of limited on-board resources, based on the comparison of some typical information security protection designs, this paper summarized the characteristics and security threats of the communication satellites, analyzed the constraints on improved security protection capabilities, then proposed a sort of collecting satellite security data by using space based probe technology, built data analysis platform and integrated monitoring system based on the ground system, which could realized the system security status monitoring and security alarm on the premise of ensuring the normal operation of the satellite business and low resource occupancy.At last the actual operation of the system was analyzed and verified.